How business intelligence maturity enabling hospital agility. Issue 1 (February 2017) - Shen, Cheng-Che; Chang, Ray-E; Hsu, Ching Jou; Chang, I-Chiu
Highlights: The current volume of information accumulated in hospitals has exceeded the capacity of their medical information systems. Some hospitals employ business intelligence systems (BIS) to extract correct, timely, and useful information for hospital decision-makers. Medical information quality was significantly influenced by BIS maturity. Medical information quality exerted a significant effect on medical decision quality, BIS usage, and user satisfaction. The positive influence of user satisfaction on medical decision quality is also noted. Abstract: Executives of information officers polled agree that rapid and accurate decision-making are essential to organizational agility and data plays an important role in decision making process. With Advanced information technologies, collecting data can be ubiquitously. However, the current volume of data accumulated in hospitals has exceeded the capacity of their medical information systems, not to mention using the data to make decisions. Hospitals started to employ business intelligence systems (BIS) to extract correct, timely, and useful information for hospital decision-makers. Most studies in the area focus on the establishment and related benefits of BIS. This research aims to evaluate the BIS maturity and its influences on decision quality to reveal the BIS impacts on hospital agility. To test the research model, opinions were collected by distributing questionnaires to clinical and administrative decision-makers who had experiences of using BIS in hospitals. The results showed that medical information quality was significantly influenced by BIS maturity. Furthermore, medical information quality exerted a significant effect on medical decision quality, BIS usage, and user satisfaction. The positive influence of user satisfaction on medical decision quality is also verified.